Preimplantation genetic testing for monogenic disorders to prevent MSH6 germline pathogenic variant related colorectal cancer - Wenhua Wang; Zheng Zhou; Xi Cheng; Li Chen; Jun Jing; Chao Chen; Jie Dong; Hui Chen; Jinzhao Ma; Bing Yao (BMC Cancer)
Abstract Background Colorectal cancer (CRC) is the third most deadly cancer in the world, accounting for approximately 10% of all cancer diagnoses and cancer-related deaths worldwide each year. In addition to recognized risk factors such as obesity, physical inactivity, and smoking, genetic predispositions significantly contribute to the risk of CRC. Methods Whole -exome sequencing (WES) was performed on a proband from a Chinese family diagnosed with CRC to identify potential variants. A germline pathogenic variant of the MSH6 gene was confirmed by Sanger sequencing. Immunohistochemistry (IHC) was used to verify the protein expression of MSH6 in the tumor sections. Prior to chemotherapy, the proband’s semen was cryopreserved in the Department of Reproductive Medicine. Preimplantation genetic testing for monogenic diseases (PGT-M) was subsequently employed to prevent vertical transmission of the pathogenic variant to the next generation. Results We confirmed a novel germline pathogenic variant of the MSH6 gene, c.3438 + 245_4082delinsTGAGACTACATTG, through WES and Sanger sequencing and verified MSH6 protein expression in tumor sections via IHC analysis. Finally, a healthy pregnancy was achieved via PGT-M technology. Conclusions Our study revealed a novel MSH6 germline pathogenic variant in CRC and expanded the spectrum of MSH6 variants involved in tumorigenesis. This study provides new insights into CRC caused by MSH6 germline pathogenic variants and demonstrates the potential application of PGT-M technology as an assisted reproductive method to prevent the vertical transmission of hereditary tumors.